Effect of Natural Food Antioxidants against LDL and DNA Oxidative Changes - Sotirios Kiokias; Charalampos Proestos; Vassilki Oreopoulou (MDPI AG, 2018)
Radical oxygen species formed in human tissue cells by many endogenous and exogenous pathways cause extensive oxidative damage which has been linked to various human diseases. This review paper provides an overview of lipid peroxidation and focuses on the free radicals-initiated processes of low-density lipoprotein (LDL) oxidative modification and DNA oxidative damage, which are widely associated with the initiation and development of atherosclerosis and carcinogenesis, respectively. The article subsequently provides an overview of the recent human trials or even in vitro investigations on the potential of natural antioxidant compounds (such as carotenoids; vitamins C and E) to monitor LDL and DNA oxidative changes.